An exploration of recommender systems explanation paradigms: generating and evaluating syntactic, semantic, and generative models with knowledge graphs: An Extended Abstract - Zanon, André Levi; Rocha, Leonardo C. Dutra da; Manzato, Marcelo Garcia (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Recommender Systems (RS) generate suggestions for users based on their past interactions and the interactions of other users. However, because RS rely on identifying similarities between users, they may expose users to a limited range of content. In addition, as algorithms have become increasingly complex, users often cannot understand why a recommendation is generated. In this thesis, we explored three approaches—syntactic, semantic, and generative—to generate explanations for recommendations and investigate their potential impact on the diversity of recommendations, with the goal of broadening user interests. Our results show that explanations can play an important role in increasing item diversity, thereby helping mitigate filter bubble effects. We also observed an improvement in the explanation quality across the approaches, from syntactic to semantic and finally to generative models.